2020
DOI: 10.3390/nu12123734
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamins D, B9 and B12 in Greek Patients with Inflammatory Bowel Diseases

Abstract: Deficiencies in vitamin D, folate and cobalamin are common in Inflammatory Bowel Disease (IBD). The aim of the present study was to assess serum levels of these vitamins in IBD adults based on the respective serum cut off values for vitamin deficiencies, and to explore possible associations with IBD-related biomarkers and nutritional intake. A cross-sectional study was carried out and patients with Crohn’s disease (CD) or ulcerative colitis (UC) from Attica-Greece were enrolled. Medical and dietary history, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In line with this, Gioxari and colleagues have recently reproduced these observations in a cohort of Greek IBD patients where they reported a serum deficiency in vitamin D, B9 and B12 in 36.8, 18.4 and 5.7% of patients, respectively. They also correlated these serum metabolite levels with clinical information and pointed to the serum vitamin profile as a complementary biomarker for the evaluation of the disease activity [111]. On the other hand, Weng and colleagues have recently reported that the levels of other vitamins compounds such as vitamin B2 (riboflavin) and nicotinate are significantly reduced in faecal samples from both UC and CD patients compared with healthy controls.…”
Section: Food Components and Xenobioticsmentioning
confidence: 98%
“…In line with this, Gioxari and colleagues have recently reproduced these observations in a cohort of Greek IBD patients where they reported a serum deficiency in vitamin D, B9 and B12 in 36.8, 18.4 and 5.7% of patients, respectively. They also correlated these serum metabolite levels with clinical information and pointed to the serum vitamin profile as a complementary biomarker for the evaluation of the disease activity [111]. On the other hand, Weng and colleagues have recently reported that the levels of other vitamins compounds such as vitamin B2 (riboflavin) and nicotinate are significantly reduced in faecal samples from both UC and CD patients compared with healthy controls.…”
Section: Food Components and Xenobioticsmentioning
confidence: 98%
“…Studies in literature also reported that serum vitamin profile could be used as a complementary biomarker, along with serum and stool inflammatory biomarkers, to assess disease activity. [38] Further, nutrigenomics studies associated micronutrients like vitamin D, vitamin E, calcium, FA, retinol and nicotinic acid that played a role in gene expression with reduced DNA damage and recommended that they be administered at an adequate dose for the treatment of patients with CD as they played a role in inflammation. [35] Our study has some limitations; first is that it has a retrospective design in a single center.…”
Section: Patientmentioning
confidence: 99%
“…Serum folate and vitamin B12 levels are inversely related to inflammatory markers and disease clinical activity in IBD patients. Therefore, there is a possibility that folate and vitamin B12 supplementation not only increases HGB levels but also reduces disease clinical activity [37,38].…”
Section: Anemia Management In Inflammatory Bowel Disease Patientsmentioning
confidence: 99%